A new video image encryption algorithm based on improved composite mapping - Tu Li; Liu Zhen; Wang Yan; Yang Gelan (ITM Web of Conferences, 2025)
In order to improve the security and efficiency of image and video encryption and improve the speed of video encryption, in this study a new video image encryption algorithm is proposed based on Arnold mapping and a kind of improved Logistic chaotic mapping. Firstly, imported a video to be encrypted and read in the specified frame image, performed a scrambling by using Arnold mapping, then generated a chaotic sequence by using improved Logistic chaotic mapping, and performed type conversion on this sequence; performed XOR operation on the scrambled matrix to obtain the diffusion matrix, then obtain a ciphertext frame image. The simulation results show that: the histogram of the encrypted image is uniformly distributed, the encryption algorithm is very sensitive to the initial key, and the initial value sensitivity performance reaches10-13, it takes only 7.9 seconds to encrypt a 328 frame video by using this algorithm, and it takes only 5.4 seconds to decrypt this video. This encryption algorithm can well resist the attack of statistical analysis and it has a good encryption effect on video.